Perceived benefits of pet ownership for the elderly with type 2 diabetes mellitus - Hugues H., Beatriz (2016)
The aim of this study was to explore the perception of senior people with diabetes mellitus type 2 (DM2) (n=60) on having companion animals and the relationship with personal satisfaction, benefits on mental health and metabolic control, and to the motivation on practicing physical activities. A self-administered questionnaire was developed for the evaluation of these aspects and for obtaining demographic data. The results showed that 82% of the persons indicated to be satisfied in sharing their life with companion animals, 88% perceived a high beneficial relationship for their mental health, and 97% indicated that having pets encouraged them to take better care of DM2. Moreover, most of the people doing walks with their dogs (15/60) admitted more eagerness for these walks (84%) and for exercise (68%).